The Impact of EFL Students’ Emotioncy Level on Their Motivation and Academic Achievement: A Theoretical Conceptual Analysis - Zhang, Xuena (Frontiers in Psychology, 2021)
Recently, teachers’ and language learners’ emotional status has received special attention among researchers. They argued that learners’ emotioncy level might affect every aspect of language teaching process; therefore, the present study reviewed the impact of EFL students’ emotioncy level on their motivation and academic achievement. Reviewing the literature revealed that there are different classifications for learners’ emotioncy level. However, studies showed that the most prominent classification of learners’ feeling is positive or negative. No matter positive or negative, the main responsibility of teachers in these situations is finding an appropriate way to control these feeling. The paper concludes with some pedagogical implications to control emotioncy in the classroom.